2000
DOI: 10.1094/pdis.2000.84.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Application of Candida saitoana and Glycolchitosan for the Control of Postharvest Diseases of Apple and Citrus Fruit Under Semi-Commercial Conditions

Abstract: The efficacy of the combination of Candida saitoana with 0.2% glycolchitosan (the bioactive coating) as a biocontrol treatment of postharvest diseases of apple and citrus fruit was evaluated in tests with natural inoculations that simulated commercial packinghouse conditions. The growth of C. saitoana in apple wounds and on fruit surfaces was not affected by glycolchitosan. The bioactive coating was more effective in controlling decay of several cultivars of apples (Red Delicious, Rome, Golden Delicious, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 16 publications
3
46
0
3
Order By: Relevance
“…Chitosan coatings reduced two of the main postharvest diseases of strawberries and raspberries, the gray mold, and Rhizopus rot (Bautista-Ban˜os et al, 2006). Control of Penicillium expansum on apples and citrus fruits has been also reported (El Ghaouth, Smilanick, Brown, Wisniewski, & Wilson, 1999). Chitosan films were also effective against fungi A. phoenicis and P. stoloniferum, which are common deteriorative to grapes, and cereal and nuts, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Chitosan coatings reduced two of the main postharvest diseases of strawberries and raspberries, the gray mold, and Rhizopus rot (Bautista-Ban˜os et al, 2006). Control of Penicillium expansum on apples and citrus fruits has been also reported (El Ghaouth, Smilanick, Brown, Wisniewski, & Wilson, 1999). Chitosan films were also effective against fungi A. phoenicis and P. stoloniferum, which are common deteriorative to grapes, and cereal and nuts, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…With reference to biocontrol agents as additional antifungal ingredients in chitosan-based coatings, El-Ghaouth, et al [92] assessed the effectiveness of a 0.2% glycolchitosan coating formulated with the antagonistic yeast Candida saitoana against citrus green mold. They observed that this bioactive coating was superior to stand-alone glycolchitosan and C. saitoana treatments in controlling green mold on different orange and lemon cultivars, and the control level was equivalent to that with IMZ.…”
Section: Chitosan Coatings Amended With Other Antifungal Ingredientsmentioning
confidence: 99%
“…Candida species are the most frequently mentioned genera of antagonists in many investigations for instance C. guillermondi, C. oleophila (Saligkarias et al 2002), C. sake (El-Ghaouth et al 2000, 2003Vinas et al 1998), and Korsten (2002) described C. saitoana as a factor limiting the development of gray mold and rot in storage of fruits and vegetables. From 17 isolates of C. albidus, no antagonistic interaction were detected.…”
Section: Resultsmentioning
confidence: 99%